THE EFFECT OF CREATIVITY LEARNING MODEL TOWARD LEARNING MOTIVATION AND SCIENCE PROCESSING SKILL OF FOURTH GRADE STUDENTS IN SCIENCE COURSE - Kadek Suardani; I Gusti Ayu Tri Agustiana; Ignatius I Wayan Suwatra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
Growing learning motivation and science processing skill are very difficult because of limited learning time at school which result in the application of learning motivation and science processing skill less than optimal. Through application creativity learning model, it is expected to be able to achieve the objectives of this research which is to analyze creativity learning model toward learning motivation and science processing skill. This research classified into quasi-experimental and the design was non-equivalent post-test only control group. All fourth-grade students belonged to the population, contained 8 classes with 184 students. Technique for sample selection was random sampling and got experimental class with 31 students and control class with 30 students. Research instrument consist of questionnaire and essay test. Manova test was used to analyze the data and continue with LSD test. From the reseach, the result showed the significant effect toward learning motivation and science processing skill that proven by significance score 0.000 that means less than 0.05 then Ho is rejected and based on LSD test, ∆µ was less than LSD.. The findings portrayed learning motivation and science processing skill positively influenced by creativity learning model. Creativity learning model is suitable for dealing with low learning motivation and science processing skills and would be problem solving about learning especially in the use of learning model.